Social movements and transformation of society - Martínez-Otero Pérez, Valentín (Pulso. Revista de educación, 2001)
We address the complex and diverse phenomenon of “social movements” in this article, which demands greater attention from the academic community, particularly the Social Sciences. Our study examines various factors that impact the emergence, evolution, and modes of action of these movements, to understand their influence on societal transformation. Given that these movements often oscillate between anti-systemic attitudes and institutionalisation, it is important to comprehensively analyse their role in contemporary democracies and their potential for facilitating citizen participation and societal progress.This article aims to shed light on some of these critical aspects.